A Study on Sexual Harassment in Small and Medium Enterprise of Malaysia - Laxman, Lekha; Omain, Siti Zaleha; Md. Som, Hishamuddin (Faculty of Management and Human Resource Development, 2006)

(untitled)
A study was conducted to analyze the problem of sexual harassment in small and medium enterprises in Malaysia. The aim of the study is to gain an understanding on the nature of sexual harassment at Malaysian workplaces. Its objectives are: to determine the level of sexual harassment awareness; to determine the types of sexual harassment and to identify type of actions normally taken by victims of sexual harassment. A quantitative study using survey methodology was employed whereby modified questionnaires designed by the DEOC Task Force on Discrimination and Sexual Harassment, USA was randomly distributed to 1000 various small and medium scale industry in the southern, central and northern industrial zone of Malaysia. The overall results show that the level of sexual harassment awareness amongst the employees in the said industries is low. Four types of sexual harassment were identified i.e. crude/offensive behavior, unwanted sexual attention, sexual coercion and sexual assault. The types of actions (if any) taken by the victims of sexual harassment consist of less serious forms such as avoiding the harasser or ignoring the behavior of sexually exploitative manners to a more serious form of action such as confronting the harasser or reporting it to the internal authorities. Though most of the victims of sexual harassment were women, men not only have reported incidences of sexual harassment but also have reported more incidences of sexual assault than the women. The study also found that there same patterns in sexual harassment in relation to certain demographic variables such as ethnicity, martial status and length of employment at a particular workplace. Various suggestions were also made to improve the working environment of the Malaysian corporate world.